Tolerance of Certain Forest Species to Varying Degree of Salinity and Alkali - Yadav, J. S. P.; Singh, K. (Indian Forester, 1970)
The results of a soil investigation conducted in February 1967 in some widely distributed saline alkali soils of Vrijbhumi Afforestation Division of Uttar Pradesh to determine the range of tolerance of some important forest species for salinity and alkali status have been reported in this paper. These soils vary widely in several morphological, physical and chemical characteristics and accordingly, the forest species have shown varying growth response. In general, all planted species have failed to grow on the soils which are compact and indurated with a cemented bed of Kankar nodules, are highly calcareous and have pH >10 and soluble salts >3.42% and >1.14% in the top soil and sub-soil respectively. P. juliflora is able to grow on the calcareous soils which have on the average a maximum pH value of 9.5 and soluble salt content of 0.54%, though a soil having pH up to 10 and soluble salts up to 1% with compact sub-soil can also be tolerated. A. arabica thrives satisfactorily on the sa1ine alkali soils which have pH value below 9 and soluble salt content below 0.3%. Azadirachta indica, Butea monosperma, Dalbergia sissoo, Pongamia pinnata and Terminalia arjuna have grown on the moderately calcareous soils which are generally non-saline and non-alkali in the top 60 cm depth but have pH up to 9.8 and soluble salts up to 0.45% in the sub-soil. Out of the species studied, Albi ia lebbek and Ailanthus excelsa appear to be the least tolerant to salinity and alkali status and require comparatively better structured soil. Further, the growth of P. juliflora brings about some improvement in the fertility status and reduction in the salinity and alkali level of the surface layer only. The trenchridge method is effective in lowering the salt concentration of the soil in the ridge by leaching. Although the technique of filling the planting pit with good imported soil helps in establishment of the planted species, it entails the possible danger of subsequent alkali development due to salt diffusion from the surrounding soil. In view of the varying degree of tolerance shown by different forest species and also wide variations encountered in the soil conditions, the paramount importance of a judicious selection of forest species according to the salinity and alkali status and morphological features of the soil is quite obvious, before any afforestation programme of saline alkali soils is undertaken.